Effect of hydrocooling, calcium chloride on the postharvest of cape gooseberry fruits (Physalis peruviana L.) - Álvarez-Herrera, Javier Giovanni; Gutiérrez-Villamil, Diego; Jaime-Guerrero, Marilcen; Carreño-López, Karen Juliana; Martínez-Osorio, John Wilson (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2024)
The cape gooseberry is an Andean fruit with significant nutritional and export potential in various international markets. The climacteric metabolism in cape gooseberry fruits results in a short post-harvest life, posing a threat to the commercialization of the fruits. Therefore, techniques are being explored to prolong the quality of the fruit. Hydrocooling (HC) and applying CaCl2 are efficient tools to enhance refrigerated storage in horticultural products. The impact of hydrocooling, CaCl2 application, and refrigeration at 4°C on the physical and chemical characteristics of cape gooseberry fruits during postharvest storage was assessed. Fruits subjected to HC exhibited reduced respiratory rate (RR) at harvest, quickly eliminating field heat. During postharvest, refrigeration extended the postharvest life of cape gooseberry fruits from 19 to 33 d. Fruits treated with HC, refrigeration, and CaCl2 (1%) demonstrated low mass loss, RR, and color index values. Additionally, they exhibited low pH values; however, this application did not significantly affect the maturity relationship. The application of CaCl2 did not affect total soluble solids (TSS), but TSS levels were influenced by HC with refrigeration, maintaining high levels until the end of storage. Therefore, it is recommended to apply HC, refrigeration (4°C), and 1% CaCl2 to cape gooseberry fruits, as this combination delays ripening and preserves post-harvest quality.